NOx Content Analysis In Ambient Air: Public Policy Perspectives And Implications For Sustainable Development In Padang City - Donny Fernandez; Genius Umar; Indang Dewata; Syamsul Amar; Ahmad Juanda (Universitas Negeri Padang, 2025)
This paper presents data from the ambient air quality monitoring of Padang City and its implications for sustainable development public policy. Urban growth and transportation and industrial activities have the potential to increase nitrogen gas emissions. Air monitoring was conducted at strategic locations in Padang City that represent anthropogenic activities. The nitrogen gas concentration data obtained were analyzed descriptively and spatially to identify the level of pollutants in the air. Monitoring results were linked to sustainable development indicators, particularly those related to public health (SDG 3) and cities and settlements (SDG 11). This paper aims to provide input for policy makers to strategize the sustainable development of Padang city.